Far away from home: Investors' underreaction to geographically dispersed information - CHEN, Zilin (Institutional Knowledge at Singapore Management University, 2022)
Using a novel data set to identify geographic peer firms based on the locations of both firms' headquarters and material subsidiaries, we show that returns on geographical peers have strong predictive power for focal firm returns. A value-weighted long-short strategy that buys stocks with the highest geo-peer returns and shorts stocks with the lowest geo-peer returns generates a Fama and French(2015) five-factor alpha of 0.6% per month. This strategy is distinct from other cross-firm momentum strategies and cannot be explained by local economic conditions. The effect is more pronounced among firms that receive less investor attention and that are more costly to arbitrage, consistent with slow information diffusion in the geographic network into stock prices.